Learning Style Preferences Among Indonesian EFL University Students: A Learning Style Survey Analysis - Muthia Sandra Riphasa; Marnita Marnita; Afdhal Dzikri; Agung Prasetya; Nurul Hidayati (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study investigated the multidimensional learning style preferences of Indonesian EFL university students using the Learning Style Survey (LSS). A quantitative descriptive survey design was employed involving 35 university students enrolled in English as a Foreign Language (EFL) courses and selected through convenience sampling. Data were collected using a questionnaire consisting of 46 items representing eleven learning style dimensions, namely Visual, Auditory, Kinesthetic, Extroverted, Introverted, Closure-Oriented, Open, Deductive, Inductive, Impulsive, and Reflective learning styles. Prior to data collection, the instrument was tested for validity and reliability, resulting in 37 valid items and high internal consistency (Cronbach’s Alpha = 0.908). The collected data were analyzed using descriptive statistics to determine the mean scores and standard deviations of each learning style dimension. The findings revealed that Reflective learning style emerged as the most preferred dimension, followed by Closure-Oriented and Visual learning styles. In contrast, Open (Perceiving) learning style showed the lowest level of preference among the participants. These findings indicate that Indonesian EFL university students tend to prefer learning environments that encourage reflection, provide clear instructional structures, and incorporate visual support during the learning process. This study contributes to the existing literature by providing empirical evidence of multidimensional learning style preferences beyond the traditional visual, auditory, and kinesthetic framework. The findings suggest that English language teachers should design instructional activities that integrate reflective learning opportunities, structured classroom procedures, visual support, and balanced deductive and inductive teaching approaches to accommodate diverse learner preferences and enhance students' learning experiences.